Evaluation of the bond-dependent factors for CFRP bars used as structural reinforcement: a critical review - Che Bakar, Mohd Basri; Muhammad Rashid, Raizal Saifulnaz; Amran, Mugahed; Jaafar, Mohd Saleh (Elsevier, 2023)
This study analyzes the precious data from the literature on bond strength between concrete and CFRP bars associated with the pullout test. In this regard, an overview of the pullout test and bond stress-slip model, along with a systematic analysis of characteristic bond strength behavior, were reviewed extensively. Over 273 specimens of CFRP bar involved in pullout tests were mined from the experimental works reported by preceding researchers worldwide. Significant findings revealed that the pullout test is a widely used method for determining the bond strength of embedded CFRP bars in concrete. The concrete compressive strength, bar diameter, modulus of elasticity, embedment length and surface treatment all have a major impact on bond performance. Moreover, the development of an analytical model for bond stress-slip is paramount to present the interaction behavior as well as to perform numerical analysis. In addition, bond strength predictions by international guidelines are conservative. However, the bond strength calculated by ACI 440.1R-15 has proven to be more practical across all the statistical measures. In line with this review, recommended research areas are also successfully discussed and proposed for further investigation.